2012
DOI: 10.1111/j.1471-4159.2012.07866.x
|View full text |Cite
|
Sign up to set email alerts
|

The new iminothiadiazole derivative VP1.14 ameliorates hippocampal damage after an excitotoxic injury

Abstract: J. Neurochem. (2012) 122, 1193–1202. Abstract Increased levels of glutamate causing excitotoxic damage accompany many neurological disorders. A well‐characterized model of excitotoxic damage involves administration of kainic acid (KA), which causes limbic seizure activity and subsequent neuronal death, particularly in the CA1 and CA3 areas of the hippocampus. Inhibition of the enzyme glycogen synthase kinase‐3 (GSK‐3) and cAMP levels might play an important role in neuroprotection. As intracellular cAMP levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Importantly, depletion of PDE7B levels by lentiviral delivery of PDE7 shRNA significantly ameliorates the motor impairment subsequent to dopaminergic cell loss. Previous results from our group demonstrate that chemical inhibition of PDE7 trigger neuroprotection and diminish neuroinflammation in different models of brain diseases, including PD (Castano et al, 2009;Morales-Garcia et al, 2011;Redondo et al, 2012;Susin et al, 2012). Other authors have shown a Fig.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Importantly, depletion of PDE7B levels by lentiviral delivery of PDE7 shRNA significantly ameliorates the motor impairment subsequent to dopaminergic cell loss. Previous results from our group demonstrate that chemical inhibition of PDE7 trigger neuroprotection and diminish neuroinflammation in different models of brain diseases, including PD (Castano et al, 2009;Morales-Garcia et al, 2011;Redondo et al, 2012;Susin et al, 2012). Other authors have shown a Fig.…”
Section: Discussionmentioning
confidence: 70%
“…As commented previously, our group has been the first to show a potent neuroprotective and anti-inflammatory effect of different PDE7 chemical inhibitors in different animal models of PD (Morales-Garcia et al, 2011;Susin et al, 2012), suggesting that this enzyme could be a promising new therapeutic target for the treatment of this devastating disorder. In this work, we show that lentiviral-mediated delivery of PDE7B small hairpin RNA (shRNA) into the SNpc of adult mice protected 80% of dopaminergic neurons and decreased glial activation after an intranigral injection of lipopolysaccharide (LPS) or 6-hydroxydopamine (6-OHDA).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Mono-substitution on position 6 of quinazoline core was crucial for effective inhibition wherein substituents of priority which possessed tight package and hydrophobicity are: Methoxy (23b, IC50 = 0.23 µM), methyl (23c, 0.10 µM), chloro (23d, 0.019 µM), thiomethyl (23f, 0.031 µM), and cyano (23p, 0.090 µM) functionalities (Takase et al, 1994) as shown in Figure 12. Administration of 3-substitutedquinazolin-2,4-dithione as optimized PDE7 inhibitor improved brain damage and enhanced behavioral aftermath in a permanent middle cerebral artery obstruction (pMCAO) stroke model (Redondo et al, 2012;Susín et al, 2012). Sánchez et al (2013) reported the inhibitory potencies of quinazoline-4-thione 24 at submicromolar levels against the catalytic domain of PDE7.…”
Section: Phosphodiesterase (Pde) Inhibitorsmentioning
confidence: 99%
“…The concentration of the different compounds was chosen based on their effectiveness in different previously published works. 8,22,31,46,47 Previously to the treatment with the test compounds, some plates were also preincubated with the PKA inhibitor H-89 (20 μM, BIOMOL Research Laboratories). After treatments, cells were processed for Western blot analysis, immunocytochemistry, or nitrite release.…”
Section: ■ Conclusionmentioning
confidence: 99%